Care-Seeking for Fever for Children Under the Age of Five Before and After the Free Healthcare Initiative in Burkina Faso: Evidence from Three Population-Based Surveys - Negatou M; Ouedraogo M; Donnen P; Paul E; Samadoulougou S; Kirakoya-Samadoulougou F (Dove Medical Press, 2021)
Mariamawit Negatou,1 Mady Ouedraogo,2 Philippe Donnen,3 Elisabeth Paul,3 Sekou Samadoulougou,4,5,* Fati Kirakoya-Samadoulougou1,* 1Centre de Recherche en Epidémiologie, Biostatistiques et Recherche Clinique, École de Santé Publique, Université Libre de Bruxelles, Bruxelles, Belgique; 2Institut National de la Statistique et de la Démographie (INSD), Ouagadougou, Burkina Faso; 3Centre de Recherche en Politiques et Systèmes de Santé – Santé Internationale, École de Santé Publique, Université Libre de Bruxelles, Bruxelles, Belgique; 4Centre for Research on Planning and Development (CRAD), Laval University, Quebec City, Quebec, G1V 0A6, Canada; 5Evaluation Platform on Obesity Prevention, Quebec Heart and Lung Institute, Quebec City, Quebec, G1V 4G5, Canada*These authors contributed equally to this workCorrespondence: Mariamawit NegatouCentre de Recherche en Épidémiologie, Biostatistique et Recherche Clinique, École de Santé Publique, Université Libre de Bruxelles, Bruxelles, BelgiqueTel +251911747363Email mariamawitbrouk@gmail.comBackground: In 2016, a free healthcare policy (FHP) was implemented in Burkina Faso for children under the age of five. In our study, we aimed to determine the prevalence of care-seeking for a fever in children under the age of five before and after the implementation of the FHP and to analyze the determinants of not seeking care under the FHP.Methods: The data of three nationally representative surveys were used to evaluate the trends of the prevalence of care-seeking. We performed a modified Poisson regression using a generalized estimating equation to determine the factors associated with not seeking care.Results: The prevalence for care seeking increased from 57.5% (95% CI, 54.2– 60.8) in 2014 to 72.3% (95% CI, 68.1– 76.2) in 2017. Children from the poor quintile were less likely to seek care when compared to children from the poorest quintile (prevalence ratio (PR) = 0.7 (95% CI, 0.5– 0.9)). Caregivers who did not have messages regarding malaria in the past six months were more likely not to seek care (PR = 0.8 (95% CI, 0.7– 0.9)). Caregivers of children aged 36– 59 months were more likely not to seek care compared to those aged < 12 months (PR = 1.6 (95% CI, 1.2– 2.1)). Children from the Boucle du Mouhoun region (PR = 1.9 (95% CI, 1.2– 3.2)) and the Centre-Est region (PR = 1.9 (95% CI, 1.2– 3.0)) were more likely not to seek care compared to children from the Sud Ouest region.Conclusion: Our study showed an increase in the prevalence of care-seeking after the implementation of the FHP. Even if this is encouraging, these findings highlight the critical importance of non-financial barriers to care-seeking. Maintaining FHP and tackling the barriers should be considered by policy makers to increase care-seeking.Keywords: fever, free healthcare policy, care-seeking, children under-five, Burkina Faso